Strength Optimisation of Variable Angle-Tow Composites Through a Laminate-Level Failure Criterion - Catapano, Anita; Montemurro, Marco (Journal of optimization theory and applications, 2020)
The development of additive manufacturing techniques for composite structures brought the emergence of a new class of composite materials: the variable angle-tow composites. Additive manufacturing of reinforced polymers allows the tow to be placed along a curvilinear path in each lamina. Accordingly, optimised solutions with enhanced properties can be manufactured. In this work, the multi-scale two-level optimisation strategy for composites is exploited to optimise the strength of variable angle-tow composites subject to mechanical and manufacturing constraints. At the first step of the strategy, the laminate strength is described through a laminate-level failure criterion based on tensor invariants and on the first-order shear deformation theory. The lay-up design phase makes use of quasi-trivial solutions and integrates a check on the first-ply failure in order to ensure the integrity of the whole laminate. The effectiveness of the strategy as well as of the proposed failure criterion is proven on some meaningful test cases.